Stomach Analyse of Trichogaster pectoralis - Atira Diniya; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study aims to understand stomach analysis of Trichogaster pectoralis present in thecanals at Tangkerang Barat District and Delima Disctrict has been conducted on February toApril 2013. Fish samples were captured using fishing rod and trawl once/week for 3 monthperiod. There were 87 fishes (32 males and 55 females) captured and TL is ranged from 113to 185 mm and BW ranged from 24 to 82.5 gr. Fish stomach was removed and stomachcontent was analyze using volumetric, occurence frequency.Stomach content of fish is related to their size. In small fish (TL less than 135 mm),the main food is plankton. In the relatively bigger fish (TL more than 135 mm) the main foodcrustacean and insect. Preponderance Index in the fish in general was Chlorophyta 26%,Cyanophyta 25%, Bacillariophyta 18%, Euglenophyta 1%, Insect 9%, and Crustacean 21%.Based on data obtained, it can be conclude that Trichogaster pectoralis is plankton feeder.Keyword : T. pectoralis, Trichogaster, Stomach Analysis,Preponderance Index.